IMovie : the missing manual, the book that should have been in the box - Pogue, David, 1963-; Miller, Aaron (Missing manual., 2014)
Explains how to use the latest version of the Macintosh-based digital video editing program to polish home videos, covering special effects, transitioning, narration, sound, and saving films in QuickTime and posting videos on the Web.